2007
DOI: 10.1113/jphysiol.2007.142760
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on extracellular Ca2+/K+ antagonism of inspiratory centre rhythms in slices and en bloc preparations of newborn rat brainstem

Abstract: The pre-Bötzinger Complex (preBötC) inspiratory centre remains active in isolated brainstem-spinal cords and brainstem slices. The extent to which findings in these models depend on their dimensions or superfusate [K + ] and [Ca 2+ ] (both of which determine neuronal excitability) is not clear. We report here that inspiratory-related rhythms in newborn rat slices and brainstem-spinal cords with defined boundaries were basically similar in physiological Ca 2+ (1.2 mM) and K + (3 mM). Hypoglossal nerve rhythm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…In agreement with the current literature (36,37,54), lowering the extracellular Ca 2+ concentration from 2 mM (experimental) to 1.2 mM (physiological) significantly increased the amount of time SP neurons spent in a depolarized state (Fig. 1).…”
Section: +supporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the current literature (36,37,54), lowering the extracellular Ca 2+ concentration from 2 mM (experimental) to 1.2 mM (physiological) significantly increased the amount of time SP neurons spent in a depolarized state (Fig. 1).…”
Section: +supporting
confidence: 92%
“…We sought an experimental approach that would increase the incidence of SP "UP states" and thus reduce the impact of silent periods. It has been previously shown that lowering Ca 2+ in the artificial cerebrospinal fluid (ACSF) improves spontaneous neuronal activity in vitro (36,37).…”
Section: Extracellular Camentioning
confidence: 99%
See 1 more Smart Citation
“…However, this solution was chosen for comparison of our findings with those in a previous study on the en bloc preparation of opioid-induced changes in membrane properties of respiratory neurons [60] and imaging of optical respiratory activity in both newborn rat en bloc medullas [35] and perfused juvenile rat brainstems [43]. Besides, respiratory-related nerve and cellular activities in en bloc preparations containing the active dual respiratory center seem to be similar in both types of solutions [36,47].…”
Section: Preparation and Solutionsmentioning
confidence: 60%
“…The brainstem plus spinal cord was then isolated and cut rostrally between the VIth cranial nerve roots and the caudal cerebellar artery ( Fig. 1) [37,47]. After transfer to an acrylic recording chamber (volume 2 ml for whole-cell patch clamp, 1 ml for imaging), brainstem-spinal cord preparations were superfused at a flow rate of 2.5-3 ml/min (temperature 25-26°C) with solution containing (mM) 124 NaCl, 5 KCl, 1.2 KH 2 PO 4 , 2.4 CaCl 2 , 1.3 MgCl 2 , 26 NaHCO 3 , 30 D-glucose; equilibrated with 95% O 2 and 5% CO 2 , pH7.4.…”
Section: Preparation and Solutionsmentioning
confidence: 99%